Implementasi Amanat Agung dalam Pertumbuhan Komunitas Youth di Gereja Mahanaim Community Church Semarang (Jurnal Pendidikan Agama dan Teologi, 2025)
This study aims to examine the implementation of the Great Commission in the growth of the Mahanaim Community Church Semarang youth community. The focus of the study is directed at discipleship, evangelism, and development strategies based on the principles of the Great Commission and their impact on community growth. The growth referred to is not only related to the increase in the number of members, but also concerns the depth of faith, the formation of spiritual character, and the active involvement of the younger generation in church services. The research method used is a qualitative case study approach. Data were obtained through in-depth interviews with youth leaders and community members, direct observation of development and service activities, and analysis of internal documents held by the church. Triangulation techniques were used to ensure the validity of the data and strengthen the research findings. The results show that the implementation of the Great Commission carried out systematically, directed, and consistently proved very effective in encouraging the holistic growth of the youth community. Discipleship strategies through small groups and personal mentoring play a significant role in instilling strong faith values. Evangelism implemented creatively and contextually is able to attract the interest of the younger generation to join. Meanwhile, ongoing development provides space for youth to grow in service skills and channel their potential. Thus, the implementation of the Great Commission not only impacts the quantity of members but also the spiritual quality, commitment to service, and engagement of the younger generation with the church. This research provides a practical contribution to other churches seeking to develop youth ministry through a holistic and transformative approach based on the Great Commission.